Labor Informality and the Vote in Latin America: A Meta-analysis. (May 2022) - Baker, Andy; Dorr, Dalton
ABSTRACT: Conventional wisdom among scholars of Latin American politics holds that informal workers are less participatory and less left-leaning than formal workers. Relevant empirical findings, however, are mixed and in need of synthesis. This article provides that synthesis by conducting meta-analyses on the universe of previous quantitative studies of informality and the vote. It finds that informal workers are indeed less likely to vote than formal workers, but the effect of informality is small—just four to seven percentage points. It further finds that informal workers are more likely to vote for the left, not the right, but here the effect size is even smaller. Meta-regression analyses reveal that in countries where organized professional activity among informal workers is high, gaps in turnout between the two sectors are minimal. The article concludes that the conventional wisdom over-states the individual-level political consequences of labor informality in Latin America.